2020
DOI: 10.1039/c9nr09135a
|View full text |Cite
|
Sign up to set email alerts
|

Protein unfolding by SDS: the microscopic mechanisms and the properties of the SDS-protein assembly

Abstract: Molecular dynamics simulations reveal how anionic surfactant SDS and heat unfold full-length proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 106 publications
2
29
1
Order By: Relevance
“…Therefore, the sequential formation of micelle-like structures occurs, and a decorated micelle structure is formed. Although the formation of pearl-necklace structures has been previously reported for ionic surfactants and proteins, 3,43 no evidence of these structures, within the concentration range investigated here, has been found. It is hypothesised that the driving mechanism for the pearl-necklace structure is similar to that of the decorated micelle model, where the hydrophobic residues of the micelle are preferably adsorbed at the micelle core and the hydrophilic groups remain in contact with the solvent.…”
Section: Papercontrasting
confidence: 50%
“…Therefore, the sequential formation of micelle-like structures occurs, and a decorated micelle structure is formed. Although the formation of pearl-necklace structures has been previously reported for ionic surfactants and proteins, 3,43 no evidence of these structures, within the concentration range investigated here, has been found. It is hypothesised that the driving mechanism for the pearl-necklace structure is similar to that of the decorated micelle model, where the hydrophobic residues of the micelle are preferably adsorbed at the micelle core and the hydrophilic groups remain in contact with the solvent.…”
Section: Papercontrasting
confidence: 50%
“…It is well known that SDS dissolves proteins due to the disruption of secondary bonds. [ 20 ] The high solubility of the unaged PNF foams indicates that these foams contained very few covalent crosslinks. The aging treatment polymerized the protein creating new covalent bonds, which stabilized the foams.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of further addition of high concentration of SDS after they completely unfolded, was the micellization around the protein backbone. The interaction between anionic head of SDS to the cationic group of BSA still remain while the SDS molecules were forming micelle [20]. Those SDS micelles formed bead-like along the BSA chain.…”
Section: Resultsmentioning
confidence: 97%
“…In this study, the SANS scattering data of BSA in addition of SDS below CMC fitted with the triaxial ellipsoid model, a simple shape approach for protein globular structure. It is previously reported that the initial interaction of SDS and protein is the binding of SDS molecule to the loop and the b-sheet part [20]. The addition of 2mM SDS led to invasion of SDS molecule to the loop of BSA and it seemed that the further addition of 5mM SDS still happened in the loop part as BSA do not have b-sheet content.…”
Section: Resultsmentioning
confidence: 98%